Effect of the cardio respirator activity in the frame of the benefit in some biochemical parameters - Beqa, Gentiana; Elezi, Abdulla; Miftari, Florian; Gjinovci, Bahri; Elezi, Gresa (Journal of Education, Health and Sport, 2018)
The study was intended to determine changes in lipid and blood glucose levels prior to and after the application of the cardio-respiratory program. Twenty-five 20-30 year old women have been tested and willingly admitted to be part of this research. At the beginning and after the completion of the cardiovascular program these biochemical parameters were determined in the sample of the testes: Glucose in the blood (GLBL), Lipoproteins High-density lipoprotein in the blood (HDLBL), Lipoproteins Low-density lipoprotein in the blood (LDLBL) , Triglycerides in the blood (TGBL). After determining the biochemical values at the beginning of the survey, the subjects were subjected to a quarterly cardio-respiratory program with a total of 36 sessions of 60 minutes. The cardio-respiratory program has included running at 50-70% intensity. For the calculation of the results obtained from the measurements of biochemical values, the basic statistical parameters have been calculated. For the assessment of the difference between two dependent groups in arithmetical means, the t-testing (Paired Sample T-Test) has been applied. The results obtained after statistical processing show that the 50-70% intensity quarterly cardio-respiratory program has had a significant effect on the normalization of lipid and blood glucose levels.